Polypropylene cable material with multi-layer structural form and test evaluation method thereof

By adding norbornene calcium dicarboxylate salt, nanomagnesium oxide and elotite nanotubes to the polypropylene cable material, the crystallinity and thermal stability of polypropylene are improved, and the polypropylene cable material is solved by adding high temperature or long-term heat. The problem of short service life under conditions has been solved, and a longer service life and better thermal oxygen aging performance has been achieved.

CN119119633APending Publication Date: 2024-12-13BINZHOU POWER SUPPLY COMPANY OF STATE GRID SHANDONG ELECTRIC POWER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410086783.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing polypropylene cable materials have a short service life under pyrolysis conditions with higher temperatures or longer time, making it difficult to meet the service requirements of cable materials.

Method used

Using a polypropylene cable material formula with multi-layer structure, calcium norbornene dicarboxylate, nanomagnesium oxide and elotite nanotubes are added as fillers, and the synergistic effect of calcium norbornene dicarboxylate and nanomagnesium oxide is carried out. Improve the crystallinity of polypropylene, and improve thermal stability through the adsorption and removal of crystallization water of polar groups of elotite nanotubes.

Benefits of technology

It significantly improves the barrier effect of polypropylene cable materials on heat and oxygen, extends the service life, and meets the service requirements of cable materials under high temperature or long-term pyrolysis conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004675235680000051
    Figure BDA0004675235680000051
  • Figure BDA0004675235680000061
    Figure BDA0004675235680000061
  • Figure BDA0004675235680000071
    Figure BDA0004675235680000071
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, and particularly discloses a polypropylene cable material with a multilevel structural form and a test evaluation method thereof. The polypropylene cable material is prepared from the following components in parts by weight: 80 to 84 parts of polypropylene homopolymer, 1.2 to 1.6 parts of filler, 0.2 to 0.4 part of norbornene dicarboxylate calcium salt and 0.2 to 0.4 part of antioxidant, wherein the filler is prepared from nano magnesium oxide and halloysite nanotubes. The polypropylene cable material disclosed by the invention has a relatively good barrier effect on heat and oxygen, the thermal stability of polypropylene is improved by adding the halloysite nanotubes, and the antioxidant can more sufficiently play a role in thermal oxidative aging resistance, so that the thermal oxidative aging rate of the polypropylene cable material is reduced, and the service life of the polypropylene cable material is prolonged. Even under the condition of high temperature or long-time pyrolysis, the cable material can have a long service life, and the service requirements of the cable material can be fully met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cable materials, and more specifically, to a polypropylene cable material with a multi-layered structure and a test and evaluation method thereof. Background Art

[0002] Polypropylene materials have a wide range of uses and are one of the important research directions in the field of power cable materials. They are expected to be used to replace cross-linked polyethylene cable materials in the future. When polypropylene materials are used as cable materials, the monomers mainly adopt the form of isotactic copolymerization, that is, isotactic polypropylene. The molecular chain of isotactic polypropylene has a helical structure. Depending on the crystallization conditions, the crystal phase of isotactic polypropylene can include monoclinic crystal (α crystal), trigonal crystal (β crystal) and orthorhombic crystal (γ crystal) and other crystal forms, among which α crystal form is the most common. Compared with α crystal, β crystal is more sparsely arranged inside, with larger spherulite size and lamellar interlayer. α crystal is characterized by better hardness and rigidity, while β crystal is characterized by better impact strength and transparency. Studies have found that isotactic polypropylene crystallizes to form α crystal under conventional cooling conditions, but melt shearing and β crystal nucleating agent (β-NA) and other methods can induce the formation of β crystal, and γ crystal can be produced under pressure induction, but it is extremely unstable and will transform into α crystal before melting. In addition to the crystalline regions composed of the above-mentioned various crystal forms, in polypropylene, due to the restriction of the long chain structure on the movement of the chain segments, coupled with the changes in the local bond length and bond angle in the chain and the local displacement of the chain, there will be a certain number of lattice defects in the crystals of polypropylene, which will affect the degree of perfection of the crystals and form quasi-crystalline structures or amorphous regions. Therefore, in polypropylene materials, due to the coexistence of crystalline regions and amorphous regions, a more complex and changeable multi-level structural morphology is often formed. Adjusting the structural hierarchical morphology of polypropylene is an important means to improve the performance of polypropylene materials.

[0003] In the related art, there is a polypropylene cable material, which includes the following components in parts by weight: 100 parts of polypropylene resin, 0.9 parts of talc, 0.5 parts of antioxidant, 1.4 parts of polyethylene wax, 3.8 parts of POE, 10 parts of ammonium polyphosphate, 0.7 parts of ultraviolet absorber, and 1.2 parts of filler; the antioxidant is antioxidant 168, the ultraviolet absorber is UV-531, and the filler is modified clay, which is prepared according to the following method: the clay is dried at 100°C for 4 hours and then put into a blender at 100°C, the fatty acid extracted from kale seed oil is added to 3 times the weight of anhydrous ethanol, stirred until mixed evenly, and then added to the blender, stirred at 300 rpm for 30 minutes, then discharged and filtered, the obtained filter cake is repeatedly rinsed with anhydrous ethanol, crushed after vacuum drying, and ground and sieved through a 150-mesh sieve to obtain the modified clay.

[0004] With respect to the above-mentioned related technologies, the inventors believe that although antioxidants are added to the polypropylene cable materials in the related technologies, polypropylene itself is a semi-crystalline polymer with limited crystal density, which makes it difficult to fully hinder the diffusion of oxygen and heat. Therefore, under the conditions of high temperature or long pyrolysis time, the polypropylene cable materials in the related technologies have a short service life and are difficult to fully meet the service requirements of cable materials. Summary of the invention

[0005] The polypropylene cable material in the related art has a short service life under the pyrolysis conditions of high temperature or long time. In order to improve this defect, the present application provides a polypropylene cable material with a multi-layer structure and a test and evaluation method thereof.

[0006] In the first aspect, the present application provides a polypropylene cable material with a multi-layer structure, which adopts the following technical solution: A polypropylene cable material with a multi-layer structure comprises the following components in parts by weight: 80-84 parts of a polypropylene homopolymer, 1.2-1.6 parts of a filler, 0.2-0.4 parts of a calcium salt of norbornene dicarboxylic acid, and 0.2-0.4 parts of an antioxidant. The filler comprises nano-magnesium oxide and halloysite nanotubes, and the halloysite nanotubes and nano-magnesium oxide are mixed in a weight ratio of (5-10):1.

[0007] By adopting the above technical scheme, the present application adjusts the formula of polypropylene cable material, adds calcium salt of norbornene dicarboxylate, and preferably uses nano magnesium oxide and halloysite nanotubes as fillers together to obtain polypropylene cable material. Nano magnesium oxide can play a synergistic role in promoting nucleation with calcium salt of norbornene dicarboxylate in polypropylene cable material, making the grain arrangement of polypropylene more uniform and dense, helping to increase the crystallinity of polypropylene, and improving the heat and oxygen barrier effect of polypropylene cable material. On the one hand, halloysite nanotubes can adsorb the primary decomposition products produced during the combustion of polypropylene through the polar groups on the inner and outer surfaces of their own tube walls, and on the other hand, they can also play a barrier role in mass transfer during the combustion process. In addition, the halloysite nanotubes will remove a part of the crystal water when heated, so the addition of halloysite nanotubes can improve the thermal stability of polypropylene. Since the polypropylene cable material of the present application has a relatively high degree of crystallinity and has a good barrier effect on heat and oxygen, and the addition of halloysite nanotubes increases the thermal stability of polypropylene, the antioxidant can more fully play its role in resisting thermal oxidative aging, thereby reducing the thermal oxidative aging rate of the polypropylene cable material. Even under pyrolysis conditions at high temperatures or for long times, it can exhibit a longer service life and can more fully meet the service requirements of the cable material.

[0008] Preferably, the polypropylene homopolymer is formed by mixing isotactic polypropylene and syndiotactic polypropylene in a weight ratio of (5-15):1.

[0009] By adopting the above technical scheme, the present application optimizes the composition of the polypropylene homopolymer. Although the crystallinity of syndiotactic polypropylene is usually lower than that of isotactic polypropylene, the addition of a small amount of syndiotactic polypropylene can promote the crystallization of polypropylene, thereby enhancing the barrier effect of polypropylene cable material against oxygen and heat, and helping to extend the service life of polypropylene cable material.

[0010] Preferably, the polypropylene homopolymer is formed by mixing isotactic polypropylene and syndiotactic polypropylene in a weight ratio of (5-10):1.

[0011] By adopting the above technical solution, the present application further optimizes the composition of the polypropylene homopolymer, which helps to extend the service life of the polypropylene cable material.

[0012] Preferably, the halloysite nanotubes and nano-magnesium oxide are mixed in a weight ratio of (5-7):1.

[0013] By adopting the above technical solution, the present application optimizes the weight ratio of halloysite nanotubes and nano-magnesium oxide, which helps to extend the service life of polypropylene cable materials.

[0014] Preferably, the filler further comprises modified montmorillonite, wherein the modified montmorillonite is montmorillonite with sodium benzoate loaded on the particle surface, and the amount of the modified montmorillonite is 10-30% of the total weight of the nano-magnesium oxide and the halloysite nanotubes.

[0015] By adopting the above technical solution, the present application optimizes the composition of the filler and adds modified montmorillonite to the filler. The sodium benzoate loaded on the surface of the modified montmorillonite can promote the nucleation of polypropylene together with the calcium salt of norbornene dicarboxylic acid and nano magnesium oxide during the molding process of the polypropylene cable material, thereby improving the crystallinity of the polypropylene, enhancing the heat and oxygen barrier capacity of the polypropylene cable material, and helping to extend the service life of the polypropylene cable material.

[0016] Preferably, the modified montmorillonite is prepared according to the following method: Sodium benzoate is added to a mixed solution of water and ethanol, and after ultrasonic dispersion, a sodium benzoate solution with a mass fraction of 2-4% of sodium benzoate is obtained, which is set aside; montmorillonite is added to the sodium benzoate solution at a weight ratio of 1:(5-10) to obtain a mixed solution, the mixed solution is heated and stirred, and then the mixed solution is dried to constant weight, and the dried product is ground to obtain modified montmorillonite.

[0017] By adopting the above technical scheme, the present application first prepares a sodium benzoate solution, then uses the sodium benzoate solution to soak montmorillonite, and loads the sodium benzoate onto the surface of montmorillonite particles through heating, stirring and drying to obtain modified montmorillonite.

[0018] Preferably, the mass fraction of sodium benzoate in the sodium benzoate solution is 3-4%.

[0019] By adopting the above technical solution, the present application optimizes the mass fraction of sodium benzoate in the sodium benzoate solution, increases the total amount of sodium benzoate loaded on the surface of montmorillonite particles, and helps to extend the service life of polypropylene cable materials.

[0020] Preferably, in the method for preparing the modified montmorillonite, montmorillonite is added to a sodium benzoate solution at a weight ratio of 1:(8-10).

[0021] By adopting the above technical solution, the present application optimizes the dosage ratio of montmorillonite and sodium benzoate solution, increases the total amount of sodium benzoate loaded on the surface of montmorillonite particles, and helps to extend the service life of polypropylene cable materials.

[0022] Preferably, the amount of the modified montmorillonite is 20-30% of the total weight of the nano-magnesium oxide and the halloysite nanotubes.

[0023] By adopting the above technical solution, the present application optimizes the dosage of modified montmorillonite so that the sodium benzoate on the surface of the modified montmorillonite can more fully produce the effect of promoting the crystallization of polypropylene, which helps to extend the service life of the polypropylene cable material.

[0024] In a second aspect, the present application provides a method for testing and evaluating polypropylene cable materials with a multi-layered structural morphology, using the following technical solution.

[0025] A test and evaluation method for a polypropylene cable material with a multi-layer structure comprises the following steps: S1. Perform a thermal gravimetric test on any of the above-mentioned polypropylene cable materials to obtain a thermal gravimetric curve (TG curve) and a first-order differential curve of the thermal gravimetric curve (DTG curve) as well as data on conversion rate (α), heating rate (β) and temperature (T); S2. The kinetic equation of the pyrolysis reaction is derived according to the Arrhenius equation and the pyrolysis mechanism of the solid insulating material, and the equation describing the rate constant-temperature relationship and the definition of the heating rate proposed by Arrhenius are substituted into the kinetic equation to obtain the kinetic equation of the heterogeneous system under non-isothermal conditions; in this step, the kinetic equation of the pyrolysis reaction and the kinetic equation of the heterogeneous system under non-isothermal conditions both contain unknowns, and what needs to be solved are the activation energy (E), the reaction mechanism function and the apparent pre-exponential factor (A); S3. Using the Flynn-Wall-Ozawa method, first make a fitting curve of lnβ and 1 / T, then solve the slope to obtain the activation energy; S4. Calculate the activation energy under different conversion conditions. If the calculated result of the activation energy does not change with the change of the conversion rate, set the form of the reaction mechanism function according to the law of pyrolysis of solid insulating materials, and set the reaction order (n) as an unknown number. Combined with the data of step S1., correct the reaction order, and make the reaction order accurate to 1 decimal place to obtain the reaction mechanism function and its integral form; S5. When the activation energy and reaction mechanism function are known, select 5 different heating rates in the range of 5-25K / min, and use the Coast-Redfern method to perform curve fitting. If the results obtained from the 5 fitting curves are within the allowable error range, then take the average of the apparent pre-exponential factors corresponding to the 5 fitting curves. In subsequent calculations, the average value is used as the reference value of the apparent pre-exponential factor; S6. Perform an integral transformation on the kinetic equation of the thermal decomposition reaction to obtain an equation with time (t) on one end and the ratio of the integral form of the reaction mechanism function to the reaction rate constant [k(T)] on the other end. Take the mass loss reaching 5% as the criterion for the end of service life. Under this criterion, find the corresponding conversion rate data and substitute it into the integral form of the reaction mechanism function. Combine the expression of the reaction rate constant, the activation energy obtained in S3, and the apparent pre-exponential factor obtained in S5 to calculate t, which is the predicted value of the service life.

[0026] By adopting the above technical scheme, the present application determines the basic data such as conversion rate, heating rate, temperature, etc. according to the thermogravimetric experiment of polypropylene cable material, and obtains the TG curve and DTG curve, and then determines the unknown quantity to be obtained as activation energy, reaction mechanism function and apparent pre-exponential factor, and obtains them in sequence. Afterwards, by substituting the conversion rate into the reaction mechanism function for calculation, and using the obtained activation energy, apparent pre-exponential factor and temperature corresponding to the conversion rate for calculation, a specific time can be obtained, which is the time required to achieve a certain conversion rate under the selected temperature conditions, that is, the predicted value of the service life.

[0027] In summary, this application has the following beneficial effects: 1. The polypropylene cable material of the present application is added with calcium salt of norbornene dicarboxylate, which has a high degree of crystallinity and has a good barrier effect on heat and oxygen, and the addition of halloysite nanotubes also increases the thermal stability of polypropylene. The antioxidant can more fully play the role of anti-thermal oxidative aging in the cable material of the present application, thereby reducing the thermal oxidative aging rate of the polypropylene cable material, and can show a long service life even under pyrolysis conditions of high temperature or long time, which can more fully meet the service requirements of the cable material.

[0028] 2. This application determines the basic data such as conversion rate, heating rate, temperature, etc. based on the thermal weight loss experiment of polypropylene cable material, and obtains the TG curve and DTG curve, and then determines the unknown quantity to be obtained as activation energy, reaction mechanism function and apparent pre-exponential factor, and obtains them in turn. After that, by substituting specific data for calculation, a specific time can be obtained, which represents the time required to achieve a certain conversion rate under the selected temperature conditions, that is, the predicted value of the service life. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0030] Preparation example of modified montmorillonite The following is an explanation using Preparation Example 1.

[0031] Preparation Example 1 In this preparation example, the selected montmorillonite is sodium-based montmorillonite with an ion exchange capacity of 92.6 meq / 100g.

[0032] In this preparation example, modified montmorillonite was prepared according to the following method: sodium benzoate was added to a mixed solution obtained by mixing water and ethanol in a volume ratio of 1:100, and a sodium benzoate solution with a mass fraction of 2% of sodium benzoate was obtained after 50kHz ultrasonic dispersion for 20 minutes, and the solution was set aside; montmorillonite was added to the sodium benzoate solution in a weight ratio of 1:5 to obtain a mixed solution, the mixed solution was heated and stirred at 80°C, and after 5 hours, the mixed solution was dried at 80°C for 12 hours to constant weight, and the dried product was ground to obtain a modified montmorillonite of 150 mesh.

[0033] As shown in Table 1, the difference between Preparation Examples 1-5 is that the mass fraction of sodium benzoate in the sodium benzoate solution is different.

[0034] Table 1 Mass fraction of sodium benzoate in sodium benzoate solution As shown in Table 2, the difference between Preparation Examples 5-9 is that montmorillonite and sodium benzoate solution are mixed in different weight ratios.

[0035] Table 2 Weight ratio of montmorillonite to sodium benzoate solution sample Montmorillonite:Sodium Benzoate Solution Preparation Example 5 1:5 Preparation Example 6 1:6 Preparation Example 7 1:8 Preparation Example 8 1:9 Preparation Example 9 1:10 Example

[0036] Examples 1-5 The following description is given by taking Example 1 as an example.

[0037] Example 1 This embodiment provides a polypropylene cable material with a multi-layer structure, including the following components: 80 kg of polypropylene homopolymer, 1.2 kg of filler, 0.4 kg of norbornene dicarboxylic acid calcium salt, and 0.2 kg of antioxidant; the polypropylene homopolymer has a weight average molecular weight of 5.9×10 5 The isotactic polypropylene is selected, the antioxidant is antioxidant 168, and the filler is a mixture of halloysite nanotubes and nano-magnesium oxide in a weight ratio of 10:1. The average length of the halloysite nanotubes is 0.5μm, the average outer diameter is 70nm, and the average inner diameter is 20nm; the average particle size of the nano-magnesium oxide is 45nm.

[0038] In this embodiment, a polypropylene cable material with a multi-layer structure is prepared according to the following method: a polypropylene homopolymer is added to a high mixer and mixed at a speed of 60 rpm for 5 minutes, then a filler and calcium salt of norbornene dicarboxylate are added and mixed for 15 minutes, and then an antioxidant is added and mixed for 5 minutes to obtain a mixture; the mixture is added to a twin-screw extruder for extrusion granulation to obtain a polypropylene cable material with a multi-layer structure.

[0039] This embodiment also provides a test and evaluation method for a polypropylene cable material with a multi-layer structure, comprising the following steps: S1. Conduct a thermal gravimetric test on polypropylene cable material to obtain the thermal gravimetric curve (TG curve) and the first-order differential curve of the thermal gravimetric curve (DTG curve) as well as the data of conversion rate (α), heating rate (β) and temperature (T); S2. The kinetic equation of the pyrolysis reaction is derived according to the Arrhenius equation and the pyrolysis mechanism of the solid insulating material, and the equation describing the rate constant-temperature relationship and the definition of the heating rate proposed by Arrhenius are substituted into the kinetic equation to obtain the kinetic equation of the heterogeneous system under non-isothermal conditions; in this step, the kinetic equation of the pyrolysis reaction and the kinetic equation of the heterogeneous system under non-isothermal conditions both contain unknowns, and what needs to be solved are the activation energy (E), the reaction mechanism function and the apparent pre-exponential factor (A); S3. Using the Flynn-Wall-Ozawa method, first make a fitting curve of lnβ and 1 / T, then solve the slope to obtain the activation energy; S4. Calculate the activation energy under different conversion rate conditions. If the calculated activation energy does not change with the conversion rate, set the form of the reaction mechanism function according to the law of pyrolysis of solid insulating materials, that is, f(α) = (1-α) n , and set the reaction order (n) as an unknown number, and correct the reaction order based on the data of step S1., and make the reaction order accurate to 1 decimal place to obtain the reaction mechanism function f(α) and its integral form G(α); S5. When the activation energy and reaction mechanism function are known, five different heating rates (5K / min, 10K / min, 15K / min, 20K / min, and 25K / min) are selected in the range of 5-25K / min, and the Coast-Redfern method is used for curve fitting. If the results obtained from the five fitting curves are within the allowable error range, the apparent pre-exponential factors corresponding to the five fitting curves are averaged, and in subsequent calculations, the average value is used as the reference value of the apparent pre-exponential factor; S6. Perform an integral transformation on the kinetic equation of the thermal decomposition reaction to obtain an equation with time (t) on one end and the ratio of the integral form of the reaction mechanism function to the reaction rate constant [k(T)] on the other end. Take the mass loss reaching 5% as the criterion for the end of service life. Under this criterion, find the corresponding conversion rate data and substitute it into the integral form of the reaction mechanism function. Combine the expression of the reaction rate constant, the activation energy obtained in S3, and the apparent pre-exponential factor obtained in S5. to calculate t, which is the predicted value of the service life.

[0040] The kinetic equation of the pyrolysis reaction in step S2. is in the form of: In formula (1), α is the mass fraction of the substance reacting at time t, also known as the reaction conversion rate, f(α) is the reaction mechanism function, and k(T) is the reaction rate constant.

[0041] The specific calculation formula of α is: In formula (2), W0 represents the starting mass, W T It represents the mass at a specific time and reaction temperature, W ∞ Indicates final quality.

[0042] The integral form of the reaction mechanism function is: The equation proposed by Arrhenius to describe the rate constant-temperature relationship is as follows: Substituting equation (4) into equation (1), the equation obtained is as follows: Substituting the heating rate β = dT / dt into equation (5), the equation obtained is as follows: The specific equation form of the Flynn-Wall-Ozawa method is as follows: When correcting the reaction order n, the approach taken is to shift the terms in equation (6) and integrate both sides to obtain: The approximate condition adopted by formula (8) is the case where the initial reaction temperature is low. At this time, the reaction rate is negligible, and the two ends can be integrated between 0-α and 0-T respectively.

[0043] Introducing temperature integral P(u): In formula (9), u = E / RT, and P(u) has no analytical solution in mathematics, only an approximate solution can be obtained. Therefore, α = 0.5 is used as the reference point for approximate processing, and the following formula is obtained: Dividing equation (10) by equation (8), we get: The temperature integral P(u) is approximately expressed using the Doyle integral, namely: P(u)=0.00484exp(-1.0516u) (12) When equation (12) is used for approximation, the activation energy E and temperature T obtained within the conversion rate range α are substituted into the left side of equation (11) to form an experimental curve for comparison with various possible reaction mechanism functions. After finding a reaction mechanism function curve with a large degree of overlap, the reaction order n can be adjusted based on the reaction mechanism function to obtain a reaction order accurate to one decimal place.

[0044] The equation obtained by the Coast-Redfern method is as follows: In formula (13), ln[G(α) / T 2 ] and 1 / T, the A value was obtained from the intercept, and the E value was obtained from the slope. The A value was taken as the average value under five heating rate conditions of 5K / min, 10K / min, 15K / min, 20K / min, and 25K / min, which was used as the reference value for subsequent calculations. The E value was averaged and compared with the activation energy obtained by the Flynn-Wall-Ozawa method for verification.

[0045] In S6., after performing integral transformation on equation (1), the following equation is obtained: After transformation, formula (14) can be obtained as follows: Formula (15) is the calculation formula for the predicted service life. When calculating, it is only necessary to select a specific temperature value and combine it with the conversion rate and other data under the temperature conditions to obtain the specific value of t.

[0046] As shown in Table 3, the differences between Examples 1-5 are mainly due to the different raw material ratios of the polypropylene cable material.

[0047] Table 3 Raw material ratio of polypropylene cable material Example 6 The difference between this embodiment and embodiment 5 is that the polypropylene homopolymer is prepared by mixing isotactic polypropylene and syndiotactic polypropylene in a weight ratio of 15:1, and the weight average molecular weight of the syndiotactic polypropylene is 1.8×10 5 , the syndiotacticity is 94%.

[0048] As shown in Table 4, the difference between Examples 6-10 is that the weight ratios of isotactic polypropylene and syndiotactic polypropylene are different.

[0049] Table 4 Weight ratio of isotactic polypropylene and syndiotactic polypropylene Examples 10-14 As shown in Table 5, the difference between Examples 10-14 is that the halloysite nanotubes and nano-magnesium oxide are mixed in different proportions.

[0050] Table 5 sample Halloysite Nanotubes: Nano-MgO Example 10 10:1 Embodiment 11 8.5:1 Example 12 7:1 Example 13 6:1 Embodiment 14 5:1 Embodiment 15 The difference between this embodiment and embodiment 14 is that the filler further includes modified montmorillonite, which is prepared according to the method of preparation example 1, and the amount of modified montmorillonite used is 10% of the sum of the weight of nano-magnesium oxide and halloysite nanotubes.

[0051] As shown in Table 6, the difference between Examples 15-23 is that the preparation examples of modified montmorillonite are different.

[0052] Table 6 Preparation example of modified montmorillonite sample Preparation Example sample Preparation Example Embodiment 15 Preparation Example 1 Embodiment 20 Preparation Example 6 Example 16 Preparation Example 2 Embodiment 21 Preparation Example 7 Embodiment 17 Preparation Example 3 Embodiment 22 Preparation Example 8 Embodiment 18 Preparation Example 4 Embodiment 23 Preparation Example 9 Embodiment 19 Preparation Example 5 / / Examples 23-27 As shown in Table 7, the difference between Examples 23-27 is that the percentage of the amount of modified montmorillonite used in the sum of the weight of nano-magnesium oxide and halloysite nanotubes (hereinafter referred to as the percentage of modified montmorillonite) is different.

[0053] Table 7 Proportion of modified montmorillonite Comparative Example Comparative Example 1 The comparative example provides a polypropylene cable material, comprising the following components in parts by weight: 100 parts of polypropylene resin, 0.9 parts of talc, 0.5 parts of antioxidant, 1.4 parts of polyethylene wax, 3.8 parts of POE, 10 parts of ammonium polyphosphate, 0.7 parts of ultraviolet absorber, and 1.2 parts of filler; the antioxidant is antioxidant 168, the ultraviolet absorber is UV-531, and the filler is modified clay.

[0054] The preparation method of polypropylene cable material comprises the following steps: (1) crushing kale seeds to 80 mesh with a grinder to obtain kale seed powder, adding the kale seed powder to ether at a solid-liquid ratio of 1:8 g / mL, placing the kale seed powder in an ultrasonic cleaner and extracting at 60° C. for 25 minutes to obtain an extract, filtering the extract to obtain a filter residue, and drying the filter residue in an oven at 60° C. to obtain kale seed oil; (2) adding the kale seed oil obtained in step (1) to 2 times the weight of distilled water, stirring at 80° C. for 2 hours to obtain a kale seed oil aqueous solution, then adding dropwise a 20% by mass sodium hydroxide solution at 80° C. within 1 hour, keeping warm for 2 hours, cooling to room temperature, adjusting the pH value to 3.5 with hydrochloric acid, standing for 1 hour, and then stratifying, taking out the upper layer and washing with water until neutral to obtain fatty acids; in this step, the weight ratio of kale seed oil to sodium hydroxide is 8:1; (3) drying the clay at 100° C. for 4 hours and then putting it into a blender at 100° C., adding the fatty acid obtained in step (2) to 3 times the weight of anhydrous ethanol, stirring until the mixture is uniform, and then adding it into the blender, stirring at 300 rpm for 30 minutes, discharging the mixture and filtering it, and repeatedly washing the obtained filter cake with anhydrous ethanol, vacuum drying it, and then crushing it, grinding it, and passing it through a 150-mesh sieve to obtain modified clay, wherein the weight of the fatty acid is 4.5% of the weight of the clay; (4) Weighing various raw materials, adding isotactic polypropylene resin, POE, and maleic anhydride grafted polypropylene into a high-speed mixer and mixing for 5 minutes, then adding raw materials except antioxidant 168 and mixing for 15 minutes, finally adding antioxidant and continuing to mix until uniform to obtain a mixture, putting the mixture into a twin-screw extruder, extruding and granulating at 140-200° C. to obtain pellets, and drying the pellets at 90° C. for 45 minutes to obtain a polypropylene cable material.

[0055] Comparative Example 2 The difference between this comparative example and Example 1 is that all fillers are replaced by the modified clay of Comparative Example 1.

[0056] Comparative Example 3 The difference between this comparative example and Example 1 is that the components of the polypropylene cable material do not include fillers.

[0057] Comparative Example 4 The difference between this comparative example and Example 1 is that the filler does not include nano magnesium oxide.

[0058] Comparative Example 5 This comparative example is different from Example 1 in that the filler does not include halloysite nanotubes.

[0059] Comparative Example 6 The difference between this comparative example and Example 1 is that the components of the polypropylene cable material do not include norbornene dicarboxylic acid calcium salt.

[0060] Comparative Example 7 The difference between this comparative example and Example 1 is that the components of the polypropylene cable material do not include an antioxidant.

[0061] Performance testing methods With reference to the record of "GB T 33047.1-2016 Plastic Polymer Thermogravimetry (TG) Part 1 General Rules", the cable materials of each embodiment and comparative example were subjected to a thermal gravimetry experiment to obtain a thermal gravimetry curve (TG curve) and a first-order differential curve of the thermal gravimetry curve (DTG curve) as well as data on conversion rate (α), heating rate (β) and temperature (T). The service life of the cable materials of each embodiment and comparative example was estimated according to the method recorded in Example 1, and the service life obtained in Comparative Example 1 was used as a benchmark to calculate the ratio between the service life of the cable materials of each embodiment and comparative example and the service life of the cable material of Comparative Example 1 at 50°C, and the ratio was recorded as the relative life. The results are shown in Table 8.

[0062] Table 8 Relative lifespan Combining Example 1 and Comparative Example 1 and Table 8, it can be seen that the relative life measured in Example 1 is significantly higher than that in Comparative Example 1, indicating that the cable material of the present application has a longer service life predicted by thermogravimetric analysis. According to the time-temperature equivalence principle, whether under pyrolysis conditions of high temperature or long time, the cable material of the present application can show better thermal oxidation aging resistance than the cable material of Comparative Example 1 under the same conditions, thereby being able to more fully meet the service requirements of the cable material.

[0063] It can be seen from Example 1 and Comparative Examples 2-5 and Table 8 that when nano-magnesium oxide and halloysite nanotubes are not selected as fillers, the service life of the cable material is short, indicating that the selection method of fillers in this application plays a key role in extending the service life of the cable material.

[0064] It can be seen from Example 1 and Comparative Examples 6-7 and Table 8 that when the cable material lacks one of the calcium salt of norbornene dicarboxylate and the antioxidant, the service life of the cable material will decrease to a certain extent relative to Example 1, so it is difficult to fully extend the service life of the cable material.

[0065] Combining Example 5 with Examples 6-10 and Table 8, it can be seen that the service life of the cable material of Examples 6-10 is longer than that of Example 5, indicating that within the dosage range selected in this application, the addition of syndiotactic polypropylene helps to extend the service life of the polypropylene cable material. When the polypropylene homopolymer is mixed with isotactic polypropylene and syndiotactic polypropylene in a weight ratio of (5-10):1, the service life of the cable material is relatively longer.

[0066] It can be seen from Examples 10-14 and Table 8 that when the halloysite nanotubes and nano-magnesium oxide as fillers are mixed in a weight ratio of (50-70):1, it helps to fully extend the service life of the polypropylene cable material.

[0067] It can be seen from Examples 14, 15-27 and Table 8 that, on the basis of Example 14, by adding modified montmorillonite to the cable material as a filler, the service life of the cable material can be further improved. Moreover, when the montmorillonite is mixed with the sodium benzoate solution at a weight ratio of 1:(8-10), the mass fraction of sodium benzoate is selected to be 3-4%, and the amount of modified montmorillonite is 3-5% of the sum of the weight of nano-magnesium oxide and halloysite nanotubes, the addition of modified montmorillonite can more fully improve the service life of the cable material.

[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A polypropylene cable material with a multi-layer structure, characterized in that: The polypropylene cable material comprises the following components in parts by weight: 80-84 parts of polypropylene homopolymer, 1.2-1.6 parts of filler, 0.2-0.4 parts of norbornene dicarboxylic acid calcium salt, and 0.2-0.4 parts of antioxidant. The filler comprises nano-magnesium oxide and halloysite nanotubes, and the halloysite nanotubes and nano-magnesium oxide are mixed in a weight ratio of (5-10):

1.

2. The polypropylene cable material with a multi-layer structure according to claim 1, characterized in that: The polypropylene homopolymer is prepared by mixing isotactic polypropylene and syndiotactic polypropylene in a weight ratio of (5-15):

1.

3. The polypropylene cable material with a multi-layer structure according to claim 1, characterized in that: The polypropylene homopolymer is prepared by mixing isotactic polypropylene and syndiotactic polypropylene in a weight ratio of (5-10):

1.

4. The polypropylene cable material with a multi-layer structure according to claim 1, characterized in that: The halloysite nanotubes and nano magnesium oxide are mixed in a weight ratio of (5-7):

1.

5. The polypropylene cable material with a multi-layer structure according to claim 1, characterized in that: The filler also includes modified montmorillonite, wherein the modified montmorillonite is montmorillonite with sodium benzoate loaded on the particle surface, and the amount of the modified montmorillonite is 10-30% of the total weight of the nano-magnesium oxide and the halloysite nanotubes.

6. The polypropylene cable material with a multi-layer structure according to claim 5, characterized in that: The modified montmorillonite is prepared according to the following method: Sodium benzoate is added to a mixture of water and ethanol, and a sodium benzoate solution with a mass fraction of 2-4% of sodium benzoate is obtained after ultrasonic dispersion, and the solution is set aside; montmorillonite is added to the sodium benzoate solution at a weight ratio of 1:(5-10) to obtain a mixed solution, the mixed solution is heated and stirred, and then the mixed solution is dried to constant weight, and the dried product is ground to obtain modified montmorillonite.

7. The polypropylene cable material with a multi-layer structure according to claim 6, characterized in that: The mass fraction of sodium benzoate in the sodium benzoate solution is 3-4%.

8. The polypropylene cable material with a multi-layer structure according to claim 6, characterized in that: In the method for preparing the modified montmorillonite, montmorillonite is added to a sodium benzoate solution at a weight ratio of 1:(8-10) and mixed.

9. The polypropylene cable material with a multi-layer structure according to claim 6, characterized in that: The amount of the modified montmorillonite is 20-30% of the total weight of the nano-magnesium oxide and the halloysite nanotubes.

10. A method for testing and evaluating a polypropylene cable material having a multi-layer structure, characterized in that: The following steps are involved: S1. Conducting a thermal gravimetric test on the polypropylene cable material according to any one of claims 1 to 9 to obtain a thermal gravimetric curve (TG curve) and a first-order differential curve of the thermal gravimetric curve (DTG curve) as well as data on conversion rate (α), heating rate (β) and temperature (T); S2. The kinetic equation of the pyrolysis reaction is derived based on the Arrhenius equation and the pyrolysis mechanism of the solid insulating material. The equation describing the rate constant-temperature relationship and the definition of the heating rate proposed by Arrhenius are substituted into the kinetic equation to obtain the kinetic equation of the heterogeneous system under non-isothermal conditions. In this step, the kinetic equation of the pyrolysis reaction and the kinetic equation of the heterogeneous system under non-isothermal conditions both contain unknowns, and what needs to be solved are the activation energy (E), the reaction mechanism function and the apparent pre-exponential factor (A). S3. Using the Flynn-Wall-Ozawa method, first make a fitting curve of lnβ and 1 / T, then solve the slope to obtain the activation energy; S4. Calculate the activation energy under different conversion rate conditions. If the calculated result of the activation energy does not change with the conversion rate, set the form of the reaction mechanism function according to the law of pyrolysis of solid insulating materials, and set the reaction order (n) as an unknown number. Combined with the data of step S1., correct the reaction order, and make the reaction order accurate to 1 decimal place to obtain the reaction mechanism function and its integral form; S5. When the activation energy and reaction mechanism function are known, select 5 different heating rates in the range of 5-25K / min, and use the Coast-Redfern method to perform curve fitting. If the results of the 5 fitting curves are within the allowable error range, then take the average of the apparent pre-exponential factors corresponding to the 5 fitting curves. In subsequent calculations, the average value is used as the reference value of the apparent pre-exponential factor; S6. Perform an integral transformation on the kinetic equation of the pyrolysis reaction to obtain an equation with time (t) on one end and the ratio of the integral form of the reaction mechanism function to the reaction rate constant [k(T)] on the other end. Take the mass loss reaching 5% as the criterion for the end of service life. Under this criterion, find the corresponding conversion rate data and substitute it into the integral form of the reaction mechanism function. Combine the expression of the reaction rate constant, the activation energy obtained in S3. and the apparent pre-exponential factor obtained in S5. to calculate t, which is the predicted value of the service life.